Respostas

2014-03-09T22:48:43-03:00
A)a-3a+a=12
-a=12 (-1)
a=-12



b)3x-3=6
3x=9
x=3



c)2x+10=-4
2x=-14
x=-7

d)5y-15=2y+3
3y=18
y=6



e)4x-4-6x-8=6
-2x=18
x=-9
1 5 1
A melhor resposta!
2014-03-09T22:51:29-03:00
a) -2a + a = 12  
    -a = 12( Multiplica por -1 )
    a = -12

b) 3x - 3 = 6
    3x = 9
      x = 9/3
     x = 3

c) 2x + 10 = -4
    2x = -4 - 10
     2x = -14
     x = 7

d) 5y - 15 = 2y + 3
    5y - 2y = 3 + 15
     3y = 18
       y = 6

e) 4x - 4 - 6x -8 = 6
    -2x - 12 = 6
     -2x = 18 ( multiplica por -1 )
      2x = -18
       x = -9
1 5 1